Új helyzetben - paradigmaváltás a határon átnyúló kapcsolatokban - Baranyi, Béla (Közép-Európai Közlemények, 2010)
The strengthening of the European integration – including the unfurling of the Schengen process – will probably lead to a radical change, in other words a paradigm shift as regards the character, content and forms of cross-border relations. The new dimensions of the border relations mean the growing importance of smaller scale, bi- and trilateral institutionalised interregional cooperations, primarily along the internal Schengen borders. In the framework of the larger scale cross-border organisational structures (Euroregions), and/or besides these the smaller scale cross-border cooperations (micro-region to micro-region, micro-region to town, town to town, associations of towns and municipalities – quasi “miniature Euroregions”) are gaining importance; also, the role of the gateway functions of the middle and big cities and the role of the other intermunicipal relations is strengthening. In the case of Hungary and the neighbours on the other side of the internal Schengen borders, the border regions and the cross-border cooperation may promote the strengthening of the connecting (bridging) role, the reorganisation of the past integrations, the “reunification” of the spatial units torn apart by the Treaty of Trianon – in the optimal case the birth of a new transnational macro-regional economic space in the Carpathian Basin.